Decolonisation and legal knowledge : reflections on power and possibility - Adébísí, Folúké (Book collections on Project MUSE., 2023)
The law is heavily implicated in creating, maintaining, and reproducing racialised hierarchies which bring about and preserve acute global disparities and injustices. This essential book provides an examination of the meanings of decolonisation and explores how this examination can inform teaching, researching, and practising of law.